Isolated Mediterranean foraging: wild greens in the matrifocal community of Olympos, Karpathos Island, Greece - Andrea Pieroni; Naji Sulaiman; Julia Prakofjewa; Shiekh Marifatul Haq; Dauro M. Zocchi; Nikos Krigas; Vassiliki Chryssanthopoulou; Renata Sõukand (BMC, 2024)
Abstract Background Studies on the in-depth documentation of wild greens use in the Mediterranean Diet (MD) are vital to understanding patterns of cross-geographical change in wild food ingredients in the Mediterranean context, their appreciated taste, and possible evolution. Our present study aims to document the leafy, wild-sourced plant portion of the MD in the unique and isolated matrifocal community of Olympos, North Karpathos Isle, Greece. Methods An ethnobotanical field study focussing on traditionally wild-sourced edible greens (chórta) was conducted during the spring of 2023 via 42 semi-structured interviews with local people. Results Our study documented 69 wild green taxa, along with their culinary uses and linguistic labels. Half of the gathered wild greens have a bitter taste (i.e. members of Asteraceae and Brassicaceae), while 70% of the top-quoted greens are bitter. These greens were mostly consumed cooked. Nearly half of the quoted taxa had been previously recorded as used in the food system of central Crete. In contrast, one-fourth of the folk phytonyms recorded in Olympos do not match the ones found in Crete and the rest of Greece, which may be linked to the Doric culture that the community remained attached to because of its isolation. However, the plant-human interaction kernel is similar to that of surrounding areas. Moreover, the community of Olympos seems to rely less on aromatic wild greens (compared with Crete). Conclusion Cross-cultural foraging comparison is crucial for better understanding the circulation, exchange, and evolution of local plant knowledge under the MD umbrella. Our study assesses, in particular, how noteworthy phytolinguistic differences indicating different ancient trajectories of cultural encounters/exchanges may not necessarily be reflected in differences in terms of plant reports. As often postulated in linguistic ethnobiology, ancient linguistic labels sometimes remain as "empty shells". Given the fragile environment and the increasing over-tourism during the summer months the study site is experiencing, the presented data could contribute to a more substantial shift towards sustainable eco-tourism initiatives involving the foraging and cooking of wild greens.